Significance of MRI Perivascular Spaces in MS - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The role of perivascular Virchow-Robin spaces was investigated in 45 multiple sclerosis (MS) patients and 30 healthy controls, in a study at Charite-Universitaetsmedizin Berlin, and Goethe University, Frankfurt.